Effects of Essential Oils to Control Penicillium Sp. In In Vitro and in In Vivo on Grapevine (Vitis Vinifera L.) Fruit. (14th September 2020) - Jahani, Mehdi; Beheshti, Mahdiyeh; Aminifard, Mohammad Hossein; Hosseini, Atefeh
ABSTRACT: The expansion of natural crop protection products as alternatives to the use of synthetic fungicides is currently popular. In this project the effects of essential oils to control Penicillium sp. in vitro and in vivo on grapevine ( Vitis vinifera L.) fruit. In the present study, the inhibitory effects of anise, chamomile, black caraway, and marjoram essential oils against Penicillium sp. tested at various concentrations (0, 200, 400, 600, and 800 μL L −1 ) in vitro and in vivo . The in vitro results showed that the growth of Penicillium sp. was completely inhibited by the application of anise oil at concentrations of 800 μL L −1 . The present results showed that the highest anthocyanin contents, total soluble solids, and pH related to the grapes treated with black caraway, chamomile, and marjoram essential oils and the lowest values belonged to the grapes treated with chamomile, marjoram, and chamomile essential oils (respectively). As well, the highest anthocyanin contents, total soluble solids, and pH associated with the control treatment, 600 and 400 μL L −1 and the lowest amounts related to a concentration of 200, 200, and 800 μL L −1 (respectively). This research confirms the antifungal effects of anise, chamomile, black caraway, and marjoram essential oils both in vitro and in vivo on grapevine fruit postharvest. Therefore, these essential oils could be an alternative to chemicals to control postharvest phytopathogenic fungi on grapevine fruit.